LANGUAGE AND LITERATURE - Teshaboyeva Nafisa Zubaydulla qizi; Xalilova Sevinch (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article discusses recent reforms in Uzbekistan and their influence on the development of language and literature. It explains how new educational programs, modern literary museums, and improved research centers support the study of the Uzbek language and honor the country’s great writers. The article also highlights efforts to preserve classical manuscripts, promote translation projects, and strengthen linguistic research. Overall, it shows how current reforms help Uzbekistan protect its literary heritage while encouraging modern growth and cultural development.